hMutSβ Is Required for the Recognition and Uncoupling of Psoralen Interstrand Cross-Links In Vitro - Zhang, Nianxiang (American Society for Microbiology, 2002)
The removal of interstrand cross-links (ICLs) from DNA in higher eucaryotes is not well understood. Here, we show that processing of psoralen ICLs in mammalian cell extracts is dependent upon the mismatch repair complex hMutSβ but is not dependent upon the hMutSα complex or hMlh1. The processing of psoralen ICLs is also dependent upon the nucleotide excision repair proteins Ercc1 and Xpf but not upon other components of the excision stage of this pathway or upon Fanconi anemia proteins. Products formed during the in vitro reaction indicated that the ICL has been removed or uncoupled from the cross-linked substrate in the mammalian cell extracts. Finally, the hMutSβ complex is shown to specifically bind to psoralen ICLs, and this binding is stimulated by the addition of PCNA. Thus, a novel pathway for processing ICLs has been identified in mammalian cells which involves components of the mismatch repair and nucleotide excision repair pathways.